Pendampingan Pendampingan Pembuatan Bahan Ajar Responsif Gender Pada Kelompok Guru Bahasa Indonesia di MTS Kabupaten Kediri - Lestari, Erawati Dwi; Mahfudhotin, Mahfudhotin (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2025)
ABSTRACTGender mainstreaming in education is a strategic effort to achieve equality and fairness in the roles of men and women. However, teaching materials used in Indonesian Language instruction at the Madrasah Tsanawiyah (MTs) level still contain gender biases that reinforce traditional role stereotypes. This program aims to assist teachers in the Indonesian Language Subject Teacher Forum (Musyawarah Guru Mata Pelajaran or MGMP) in Kediri Regency to understand, analyze, and develop gender-responsive teaching materials. The Participatory Action Research (PAR) method was applied in several stages: needs analysis, identification of gender bias in teaching modules, conducting workshops on material development, implementation, and evaluation. The results revealed significant improvements in teachers' understanding of gender bias concepts and their skills in creating inclusive and gender-equitable teaching materials. The newly developed modules incorporate texts, illustrations, and examples that reflect gender diversity in a balanced manner. This activity positively contributes to fostering a more inclusive and open learning environment, where students can embrace gender equality values free from societal role stereotypes.Keywords: gender mainstreaming, gender bias, gender-responsive teaching materials, Indonesian Language MGMP, inclusive education